Social media platforms for entertainment and creative use: An analytical study on students at King Faisal University - Saleh, Shoeb Gamal; Helali, Mamdouh Mosaad; Ibrahim, Khaled Ahmed Abdel-Al (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to assess the extent to which King Faisal University students employ critical and creative thinking skills when interacting with social media platforms. Utilizing a descriptive research design, the investigation administered a standardized scale measuring critical and creative use of social media to a sample of 507 male and female students. The results revealed that the overall level of critical and creative practices was moderate. No statistically significant differences were found in these practices based on gender or academic specialization; however, significant differences emerged across academic levels, with students at more advanced levels demonstrating higher proficiency. Moreover, a significant correlation was observed between critical and creative practices. The study concludes that the efficacy of social media platforms ultimately depends on the user’s approach. Through deliberate and balanced use, these platforms can be transformed into valuable tools for personal development, skill enhancement, and effective communication. It is recommended that university curricula incorporate courses and training programs designed to translate the theoretical aspects of critical and creative thinking into practical skills for the optimal use of social media.